Effect of Heating Duration in Free Fatty Acid and Sensory Quality of Palm Cooking Oil - Trimulya, Agung; Khairunnisa, Anis; Defira, Citra (Sriwijaya FoodTech Journal, 2025)
Palm cooking oil is extensively used for frying in both domestic and industrial settings. However, prolonged heating at high temperatures can lead to chemical and sensory degradation, compromising oil quality and consumer safety. This study aims to evaluate the effect of heating duration on the formation of free fatty acids (FFA) and changes in sensory properties of palm cooking oil. A total of ten heating durations (0 to 270 minutes, at 30-minute intervals) were applied at a constant temperature of 200 °C. FFA levels were quantified using a titrimetric method based on SNI 7709:2019, and sensory analysis was performed by trained panelists. The results showed a significant (p < 0.05) linear increase in FFA content with prolonged heating, exceeding the safety threshold of 0.30% after 90 minutes. Sensory evaluations also revealed a marked decline in aroma, taste, and color starting from the 90-minute point. These changes are attributed to thermal oxidation, hydrolysis, and polymerization reactions that accelerate lipid breakdown. The findings suggest that palm oil should not be used for frying beyond 60–90 minutes at 200 °C to ensure compliance with safety standards and maintain sensory acceptability. This study provides a quantitative basis for determining critical usage limits of palm oil in high-temperature cooking applications.